Design and engineering of multifunctional silica-supported cooperative catalysts - Fernandes, Antony E.; Jonas, Alain M. (Catalysis today, 2019)
[Display omitted] •This review covers the recent progress in the design and engineering of multifunctional silica-supported cooperative catalysts.•The concept of cooperative catalysis is briefly presented.•The different synthetic methods for the preparation of multifunctional silica-supported cooperative catalysts are described.•Critical factors such as the ratio, the proximity and the distribution of surface catalytic groups are discussed. The immobilization of multiple functional groups on mesoporous silica has provided opportunities to emulate the unique design principles and performances of enzymes. In this direction, it is essential to master the cooperative behavior of active surface-bound molecules to arrive at heterogeneous, recyclable catalysts with enhanced or novel properties compared to the parent system in solution. With the advances in sol-gel and surface chemistry, it is now possible to prepare silica-supported multifunctional catalysts that can combine most of the activation modes of organic chemistry. Further tailoring the surface ratio and proximity of the confined activating functional groups affords ways to refine the probability of synergistic interactions within the active site. Yet, the systematic evaluation and engineering of the spatial distribution of surface functional groups, which are more often randomly arranged within the pore channels, rises the next key challenge towards a more rational design of bioinspired supported catalysts.